Lech Majewski, metafizyka i Bosch - Wysłouch, Seweryna (Przestrzenie Teorii, 2023)
The subject of the analysis is the problem of metaphysics in Lech Majewski’s novel Metafizyka [Metaphysics] (2002) and in the author’s film adaptation entitled Ogród rozkoszy ziemskich [The Garden of Earthly Delights] (2004). In the novel, metaphysical sensations are conveyed through discourse: 1) the reflections of the rationalist protagonist who undergoes a crisis of worldview following the death of his partner, and 2) in interpretations of the mysterious triptych by Hieronymus Bosch, showing an irreal world: an earthly paradise which the characters attempt to emulate by repeating scenes from the painting. In the film, Majewski aban metaphysical discourse in favour of exposing The Garden of Earthly Delights and showing elaborate psychological portraits of his characters, especially the heroine who is fascinated by Bosch. Therefore, despite having the same plot, the novel and the film are two separate, autonomous works.